2004
DOI: 10.1063/1.1812588
|View full text |Cite
|
Sign up to set email alerts
|

The origin of slow electron recombination processes in dye-sensitized solar cells with alumina barrier coatings

Abstract: We investigate the effect of a thin alumina coating of nanocrystalline TiO 2 films on recombination dynamics of dye-sensitized solar cells. Both coated and uncoated cells were measured by a combination of techniques: transient absorption spectroscopy, electrochemical impedance spectroscopy, and open-circuit voltage decay. It is found that the alumina barrier reduces the recombination of photoinjected electrons to both dye cations and the oxidized redox couple. It is proposed that this observed retardation can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
1
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 191 publications
(164 citation statements)
references
References 29 publications
(47 reference statements)
5
156
1
2
Order By: Relevance
“…29, 38 Authors of one of the latter papers established that alumina shells retard the recombination dynamics of nanocrystalline TiO 2 by passivating surface recombination centers and slowing the rate of interfacial charge transfer. 39 However, we note that Al 2 O 3 coatings have been shown to improve the efficiency of only relatively inefficient devices (<5%) and that no core-shell cell has yet outperformed the best TiO 2 cells made by Grätzel et al In any case, these unpromising results discouraged further study of the ZnOAl 2 O 3 core-shell nanowire cells.…”
Section: Resultsmentioning
confidence: 74%
“…29, 38 Authors of one of the latter papers established that alumina shells retard the recombination dynamics of nanocrystalline TiO 2 by passivating surface recombination centers and slowing the rate of interfacial charge transfer. 39 However, we note that Al 2 O 3 coatings have been shown to improve the efficiency of only relatively inefficient devices (<5%) and that no core-shell cell has yet outperformed the best TiO 2 cells made by Grätzel et al In any case, these unpromising results discouraged further study of the ZnOAl 2 O 3 core-shell nanowire cells.…”
Section: Resultsmentioning
confidence: 74%
“…was shown that alumina coating improves considerably the electron lifetime by an almost complete passivation of surface trap states. 23,38 Absorption of molecules with different dipole moment modifies the energy level of a nanostructured semiconductor immersed in solution, as shown in Fig. 3 and discussed later.…”
Section: Nanoparticles and Nanostructuresmentioning
confidence: 95%
“…Therefore, both values are limited by the recombination processes 2,8,9 that occur when the photoinjected electron recombines with the oxidised dye molecule (R 1 ) or reacts with the oxidised form of the redox couple in the electrolyte (R 2 ). Process R 2 has been well studied [10][11][12][13][14] and has been deemed to have a greater impact on device performance than R 1 .…”
Section: Introductionmentioning
confidence: 99%